In the child's voice: The experiences of primary school children with social, emotional and mental health difficulties. (April 2020) - Dolton, Alice; Adams, Sarah; O'Reilly, Michelle
In England schools are increasingly responsible for supporting children with Social, Emotional and Mental Health (SEMH) difficulties yet their voices are rarely represented. Through semi-structured interviews, the views of 11 children aged 6–11 years with SEMH difficulties were sought. Using thematic analysis two themes were identified – (1) social relationships and interactions, and (2) emotional and behavioural reactions. The children demonstrated that they were articulate and reflective about the impact their difficulties have in the learning environment. For some, they reported building and maintaining close reciprocal friendships which they felt enriched their time at school. It was concluded that children with SEMH difficulties need to feel safe and supported by adults to flourish in school. This work demonstrates the importance of taking a child-centred approach, allowing children to feel heard, understood and valued.